1998
DOI: 10.1017/s1355838298971990
|View full text |Cite
|
Sign up to set email alerts
|

Cis-acting elements are required for selenium regulation of glutathione peroxidase-1 mRNA levels

Abstract: Classical glutathione peroxidase (GPX1) mRNA levels can decrease to less than 10% in selenium (Se)-deficient rat liver. The cis-acting nucleic acid sequence requirements for Se regulation of GPX1 mRNA levels were studied by transfecting Chinese hamster ovary (CHO) cells with GPX1 DNA constructs in which specific regions of the GPX1 gene were mutated, deleted, or replaced by comparable regions from unregulated genes such as phospholipid hydroperoxide glutathione peroxidase (GPX4). For each construct, stable tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 40 publications
3
64
3
Order By: Relevance
“…Nevertheless, studies in addition to those reported here offer no evidence that the PHGPx SECIS confers immunity to NMD in cultured cells: hybrid genes in which the 3Ј UTR of GPx1 mRNA was substituted for that of PHGPx mRNA generated mRNA susceptible to NMD under either Se-adequate or Se-deficient conditions (Weiss and Sunde, 1998). Furthermore, it is difficult to conceive of a SECIS element so effective that it would function with comparable efficiency regardless of the Se concentration.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Nevertheless, studies in addition to those reported here offer no evidence that the PHGPx SECIS confers immunity to NMD in cultured cells: hybrid genes in which the 3Ј UTR of GPx1 mRNA was substituted for that of PHGPx mRNA generated mRNA susceptible to NMD under either Se-adequate or Se-deficient conditions (Weiss and Sunde, 1998). Furthermore, it is difficult to conceive of a SECIS element so effective that it would function with comparable efficiency regardless of the Se concentration.…”
Section: Discussioncontrasting
confidence: 58%
“…Second, at least for the PHGPx gene of pig, which is the only characterized PHGPx gene, the sole Sec codon resides within exon 3 and is followed by four introns, all of which reside Ͼ50 -55 bp downstream of the Sec codon (Brigelius-Flohé et al, 1994). In fact, the distance between the Sec codon and the closest downstream intron for both PHGPx and GPx1 genes is 105 bp, and this intron has been shown to be critical for the NMD of GPx1 mRNA (Moriarty et al, 1997;Weiss and Sunde, 1998;Sun et al, 2000). Third, based on studies of GPx1 mRNA translation (Moriarty et al, 1998), there is no reason to think that the cotranslational insertion of Sec into PHGPx protein would not be in competition with translation termination and, therefore, NMD.…”
Section: Nmd Of Phgpx Mrna Varies With Cell Typementioning
confidence: 99%
“…A recent study posits that under Se deficiency, eIF4A3, a core component of the EJC, is up-regulated and binds the SECIS element of GPx1 but not that of GPx4, competing for binding of the Sec-incorporation factor SBP2 and ultimately inhibiting Sec incorporation (Budiman et al 2009). Although this is a plausible theory, it conflicts with a previous study (Weiss and Sunde 1998), showing that the GPx4 3 ′ UTR is not able to stabilize the Se responsiveness of GPx1 mRNA. Another explanation could relate to the relative abundance of each of two isoforms of the Sec-tRNA.…”
Section: Discussioncontrasting
confidence: 96%
“…This "hierarchical" regulation of selenoprotein expression occurs at both mRNA abundance and translational levels; however, the underlying mechanisms are not fully understood (335). The decreased mRNA abundance of stress-related selenoproteins under conditions of Se deficiency was attributed to altered rates of mRNA turnover due to nonsense-mediated decay (NMD) rather than transcriptional regulation (260,366). In eukaryotes, NMD pathway is used to eliminate mRNA transcripts with premature stop codons.…”
Section: E Regulation Of Selenoprotein Expressionmentioning
confidence: 99%